2004
DOI: 10.1099/mic.0.27392-0
|View full text |Cite
|
Sign up to set email alerts
|

The complete genomes of Lactobacillus plantarum and Lactobacillus johnsonii reveal extensive differences in chromosome organization and gene content

Abstract: The first comprehensive comparative analysis of lactobacilli was done by comparing the genomes of Lactobacillus plantarum (3?3 Mb) and Lactobacillus johnsonii (2?0 Mb). L. johnsonii is predominantly found in the gastrointestinal tract, while L. plantarum is also found on plants and plant-derived material, and is used in a variety of industrial fermentations. The L. plantarum and L. johnsonii chromosomes have only 28 regions with conservation of gene order, totalling about 0?75 Mb; these regions are not co-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 55 publications
1
60
0
2
Order By: Relevance
“…Our initial experiments confirmed that L. johnsonii NCC 533 had a growth requirement for oleic acid, and consequently Tween 80 was added to the minimal medium (4). In order to find the lowest concentration needed for uninhibited growth, a dose-response curve with oleic acid was performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial experiments confirmed that L. johnsonii NCC 533 had a growth requirement for oleic acid, and consequently Tween 80 was added to the minimal medium (4). In order to find the lowest concentration needed for uninhibited growth, a dose-response curve with oleic acid was performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…L. plantarum has the largest Lactobacillus genome sequenced to date (3.3 Mb) and has a commensurate biochemical complexity. For example, L. plantarum possesses enzymes for the biosynthesis of all amino acids except leucine, isoleucine, and valine, whereas L. johnsonii is predicted to be incapable of synthesizing any amino acids (19). L. sakei, although displaying the highest levels of orthology with L. plantarum, is unable to synthesize 18 amino acids (18).…”
mentioning
confidence: 99%
“…L. acidophilus appears to be auxotropic for 14 amino acids (17). L. johnsonii lacks the ability for de novo synthesis of purines and cofactors (16,19). In common with Streptococcus thermophilus (20), which has been passed for centuries in the nutrient-rich medium of milk, L. johnsonii and L. acidophilus appear to have undergone genome reduction in adapting to a lifestyle of close host association.…”
mentioning
confidence: 99%
“…Determination of numbers of shared orthologues revealed highest numbers with L. plantarum (61?1 % of L. salivarius proteins), followed by Enterococcus faecalis (50?4 %), L. sakei (49?8 %), L. acidophilus (46?3 %) and L. johnsonii (45?1 %); other relevant genome features are shown in Table 1. The genomes of L. plantarum and L. johnsonii have been subjected to a detailed pairwise comparative analysis (Boekhorst et al, 2004). A total of 28 regions of conserved gene order were identified, totalling 0?75 Mb, but these regions were not collinear.…”
Section: Introductionmentioning
confidence: 99%